Konveyor untuk Klasifikasi Kualitas Buah Pisang menggunakan Image Processing - Wicaksono, Immawan; Javier, Azhar Bima; Sumardi, Sumardi; Cahyadi, Widya (Fakultas Teknik, Universitas Jember, 2023)
Post -harvest processing is one of the activities to maintain the quality of bananas. Efforts made to maintain the quality of bananas are sorting. Sorting is the separation of cleaned materials into various fractions based on their physical character (shape, size, weight, type, color), chemical (odor composition and rancidity) and biological (type and damage by insects, number of microbes, and growth power). . The purpose of sorting is to determine the classification of commodities based on similar qualities contained in the commodity itself. One of the banana fruit harvesting methods that can be used is to use image processing. Image processing is the handling of text data and image data based on a visual system that has a much higher level of accuracy than human visual. One of the methods that can solve the problem is to use the Image Classification method. With the addition of these supporting methods, the identification results and the level of data accuracy will be better.